The resistance of Hajj Musa bin Al-Hassan Al-Darqawi in the land of the Ouled Nail 1834-1849 (the Ribat of Ain Al-Khadra in Qasr Al-Sharif as a model) - khedidji, houari boumediene; talibi, Ali (The Algerian Historical Journal, 2026)
The area of Ain al-Khadra, located west of Qasr al-Sharif in Jolfa, embraced the resistance of the Egyptian Sheikh Sidi Moussa bin al-Hassan al-Dimiati al-Zakzouki, who came to the area for two purposes, religious, educational and jihadist at the same time, and he established a base in it to spread his message among the residents of the palace and his followers. This led to the materialisation of his jihadist and educational project, especially after his prestige rose and people flocked to him in abundance, and we will shed light on the personality of Sheikh Musa al-Dergawi and the reasons for his choice of Ain al-Khadra, and its impact in delivering his jihadist and educational call against French colonialism.